A Theory on the Involvement of Religion in National Security Policy Formulation and Implementation: The Case of Israel before and after the Religionization of Its Security Environment - Bar-Maoz, Moria (Religions, 2020)
This article offers, for the first time, a theoretical model of religion’s influence on the formulation and execution of national security policies. To build this model, it analyses the influence of religion on Israel’s national security policymaking—before and after Israel’s security environment went through a process of religionization beginning in the 1970s. The article proposes that religion’s effect on national security policymaking is comprised of three tiers that follow one another in the decision making sequence and, yet, are independent from one another: (1) operational beliefs embedded in the state’s security thinking on the relations between religion and security; (2) opportunities and constraints on the state’s freedom of action, due to the role religion plays in global, regional and domestic politics as well as bilateral relations; and (3) governmental utilization of religion to realize national security goals. At its conclusion, the article demonstrates that the model is applicable to other countries as well, using the case of France’s policies in the 21st century.